Pembangunan Berkelanjutan dan Keadilan Sosial: Catatan Tentang Peran Perguruan Tinggi - Ohoitimur Johanis; Anselmus Jamlean (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2023)
The history of human civilization has never failed to record the reality of poverty and social injustice. The poor and those who are victims of injustice have always been among us. Today there is a new awareness that classic humanitarian problems are inseparable from environmental problems. Destruction of the environment always results in impoverishment and human suffering. And, conversely, socio-economic marginalization often occurs as a result of exclusive control over natural resources. From an ethical perspective, human and environmental issues are essentially a matter of social injustice. This article intends to trace the views of the church's social teaching on the sustainable development and social justice. Some remarks are also given concerning the role and contribution of universities thereof.